Intergenerational climate at higher education: validity of the Spanish version of the workplace intergenerational climate scale - Rodríguez-Gómez, David; Gonzalez-Ramirez, Teresa; Armengol, Carme (Frontiers in Education, 2024)
An ageing workforce and the coexistence of different generations in the same work environment has garnered the interest of practitioners and theoreticians with regard to the climate and interactions that occur between these generations. Although there are various instruments that attempt to measure the intergenerational climate in organizations, there are no studies that demonstrate the effectiveness of such instruments in the Spanish university context. This article presents the analysis of the psychometric properties of the Spanish version of the Workplace Intergenerational Climate Scale (WISCWICS) adjusted to the specific context of higher education institutions and administered to a sample of 1116 university teachers. After the analyses were carried out, an instrument with 16 items was obtained (4 less than the original questionnaire), and we can affirm that the resulting questionnaire is appropriate to measure the intergenerational climate among university teachers in the fields of teaching, research and management in the Spanish university context. However, more detailed, and individual analysis of each of the areas (i.e., teaching, research and management) would likely yield slightly different models but a better fit. theorists with regard to the climate and the interactions that occur between said generations (e.g.,